Audit committee competencies and corporate disclosure transparency of Malaysian government linked companies - Manap M.I.A.; Yaacob N.S.; Alrazi B. (Inderscience Publishers, 2023)
Transparency through corporate disclosure is crucial especially in a society that demands for real-time information. Underlying this is a belief that competency enhances the effectiveness of audit committees and, by extension, the corporate disclosure transparency. This study primarily analyses the relationship between audit committee competencies and corporate disclosure transparency of Malaysian GLCs. The competencies examined in details are experience, advanced academic qualification, training and multiple directorships. Regarding experience, it is divided into accounting financial experts, finance experts and supervisory experts. To achieve this objective, a quantitative-positivist approach has been adopted in this study wherein the aggregate disclosure index was designed and annual reports of ten GLCs for the period of 20092017 were used to collect data. Using multiple regression analysis on the data collected, the results show that accounting financial experts, finance experts and advanced academic qualification have a significant positive influence on the corporate disclosure transparency. However, there is no evidence that supervisory experts, training and multiple directorships affect corporate disclosure transparency. Copyright 2022 Inderscience Enterprises Ltd.